INVESTIGASI PENGARUH PENAMBAHAN TUGAS TERHADAP HASIL BELAJAR SISWA: TEMUAN DI SMP NEGERI 1 LEWA KELAS VII - Ochtavia Lutfi; Zulkarnain Zulkarnain (Universitas Riau, 2020)
The learning process of goodness and organized teaching staff is highly prioritized to achieve the competencies expected to all students. Ineffective delivery due to time constraints, especially in science lessons causes the learning process run unwell. Besides the discomfort in learning is also an important problem in every teaching and learning process. Often students feel bored with the material delivered too monotonous and make students not pay attention to the teacher during studying. A new method of providing additional assignments at the end of each meeting is carried out in this study to obtain a change in students' interest in learning well. This study has two cycles with stages of planning, action, observation, reflection, and the end of the action. Direct observation is applied to this research method. The results showed that the first cycle had an increase in interest in learning from pre-cycle 33.33% to 50% with 20 students who had reached the minimum threshold (KKM) and 12 students who had not either. Increased interest in learning with very good criteria occurred in the second cycle with a percentage of 83.33% in which 31 students reached the KKM and 1 student was not.